STRUCTURAL SYNTHESIS OF COMBINED ROBUST CONTROL SYSTEM WITH EXTERNAL COORDINATE DISTURBANCES - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2012)
The paper is devoted to actual problem of precision and disturbance resistant control systems. The basic approaches to design of the combined robust control systems are considered. The basic concepts of the structural -synthesis of the combined system and the optimization criterion taking into consideration the sensitivity functions by the reference signal, parametrical structured and external coordinate disturbances are defined. The expression for the transfer function of the generalized system is obtained. The possibilities of its representation in the space of states are shown. The obtained results may be used in the area of the wide class control systems.